2010
DOI: 10.1186/1748-717x-5-62
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning using MRI data: an analysis of the dose calculation accuracy for different treatment regions

Abstract: BackgroundBecause of superior soft tissue contrast, the use of magnetic resonance imaging (MRI) as a complement to computed tomography (CT) in the target definition procedure for radiotherapy is increasing. To keep the workflow simple and cost effective and to reduce patient dose, it is natural to strive for a treatment planning procedure based entirely on MRI. In the present study, we investigate the dose calculation accuracy for different treatment regions when using bulk density assignments on MRI data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(181 citation statements)
references
References 27 publications
3
175
1
2
Order By: Relevance
“…This has created great interest in the concept of using MRI for treatment planning in external beam therapy, especially Intensity-Modulated Radio-Therapy (IMRT) [123][124][125]; an MRI-based boost-dose up to 80 Gy to the dominant tumour appears to be associated with low toxicity, however cancer control outcomes are not yet available [126]. EPE on MRI was shown to be the strongest predictor of biochemical recurrence in one study of men undergoing combined brachytherapy + IMRT, which suggests it could be useful in guiding prognosis and treatment planning [127].…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…This has created great interest in the concept of using MRI for treatment planning in external beam therapy, especially Intensity-Modulated Radio-Therapy (IMRT) [123][124][125]; an MRI-based boost-dose up to 80 Gy to the dominant tumour appears to be associated with low toxicity, however cancer control outcomes are not yet available [126]. EPE on MRI was shown to be the strongest predictor of biochemical recurrence in one study of men undergoing combined brachytherapy + IMRT, which suggests it could be useful in guiding prognosis and treatment planning [127].…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…It has been shown that a clear reduction of the dose calculation error can be achieved by segmenting a few tissue types and assigning different tissue properties to them [1]. However, the clinical applicability is limited as long as a timeconsuming manual segmentation is required-an automatic method is evidently needed.…”
Section: Introductionmentioning
confidence: 99%
“…To use PET/MR data as a single imaging modality to base RT treatment planning and dose calculation on, dedicated algorithms that allow a transformation of MR values into pseudo-CT values 30 as well as a dedicated system for external-internal reference point definition are required. The definition of such isocenter point can be realized using a special laser system for RT simulation, which could be installed for combined PET/MR systems.…”
Section: Discussionmentioning
confidence: 99%